Literacy and Numeracy Ecosystem: A Case Study of Learning Quality Transformation in the Suburban Area of Semarang City - Ayu Nyoman Murniati, Ngurah; Sulanjari, Bambang; Haryati, Titik (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
This study aims to analyze the acceleration of secondary education quality based on the harmonization of managerial policies and instructional flexibility, specifically examining the use of the Education Report Card as a pedagogical navigation instrument. This study employed a qualitative approach conducted in a suburban area to explore and analyze the policy harmonization and instructional practices in both public and private secondary schools. The results reveal a dichotomy in achievement: public schools excel in digital aspects, while suburban private schools face obstacles in developing students' critical thinking. The findings confirm that literacy and numeracy success depends on cross-subject synergy and teachers' mental well-being rather than just facilities. Consequently, this study practically recommends adopting a